Perlindungan Hukum Terhadap Saksi Dan Korban Dalam Sistem Peradilan Pidana Di Indonesia - Bambang Julianto (Universitas Islam Indonesia, 2020)
One of the much needed legal evidences which is almost always present in every criminal case is witness testimony. Therefore, legal protection for witnesses and victims is very necessary to provide a sense of security and protection from all forms of fear and threats from perpetrators of criminal acts that might affect the truth in criminal justice system. This study aims to analyze the following problems: implementation of protection for witnesses and victims in the criminal justice system; how to get protection from the Witness and Victim Protection Agency (LPSK) in the criminal justice system; and obstacles of LPSK in providing protection for witnesses and victims. This research uses empirical method, whereby the data collection technique is done by interview and literature study. The results of the study indicate that the implementation of the witness and victim protection policy begins with the implementation of Law No. 13 of 2006 on the Protection of Witnesses and Victims, by reflecting the legal protection of witnesses in the United States. The procedures for applying for protection to the LPSK are regulated in LPSK Regulation No. 6 of 2010 concerning Procedures for Protection of Witnesses and Victims. Meanwhile, the obstacles include but not limited to the position of LPSK which is only in the capital city, the mindset of the law enforcement officials, and the lack of cooperation between the LPSK and other agencies.